2008
DOI: 10.1590/s0100-83582008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e nutrição mineral de Ipomoea nil

Abstract: Um experimento em casa de vegetação foi conduzido entre novembro de 2005 e abril de 2006, na UNESP, campus de Jaboticabal, SP, objetivando estudar a produção de massa seca, a distribuição e o acúmulo de macronutrientes por Ipomoea nil, uma importante infestante de culturas anuais e perenes no Brasil. As plantas foram cultivadas em vasos de 7 litros com substrato de areia e irrigadas diariamente com solução nutritiva de Hoagland & Arnon. O delineamento experimental foi inteiramente casualizado, com quatro r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
(6 reference statements)
2
7
0
3
Order By: Relevance
“…This trend was also verified for I. nil (Duarte et al, 2008). This behavior may have occurred due to the growth habit of these species.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…This trend was also verified for I. nil (Duarte et al, 2008). This behavior may have occurred due to the growth habit of these species.…”
Section: Resultssupporting
confidence: 70%
“…After this period, there was a reduction of total dry mass accumulation due to plant senescence. Duarte et al (2008) observed that I. nil accumulated more dry mass at 123 DAE; furthermore, I. quamoclit presented less dry mass accumulation than I. nil, growing under the same conditions. It was ascertained considerable dry mass accumulation from 77 to 133 DAE ( Figure 1A).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Alguns estudos foram realizados visando conhecer as curvas de crescimento e de acúmulo de nutrientes por espécies como Ipomoea nil (Duarte et al, 2008) e Solanum americanum (Bianco et al, 2010), entre outras. Esses ensaios foram realizados em casa de vegetação, mas não tiveram comparações com uma espécie cultivada.…”
Section: Introductionunclassified